Utility of the Structured Interview of Reported Symptoms (SIRS-2) in detecting feigned adult attention-deficit/hyperactivity disorder. Issue 8 (14th September 2019) - Becke, Miriam; Fuermaier, Anselm B. M.; Buehren, Jannes; Weisbrod, Matthias; Aschenbrenner, Steffen; Tucha, Oliver; Tucha, Lara
ABSTRACT: Introduction : The Structured Interview of Reported Symptoms (SIRS-2) utilizes various strategies in the detection of simulated psychiatric disorders. The present study aimed to examine which of these strategies proves most useful in uncovering feigned attention deficit hyperactivity disorder (ADHD) in adulthood. Method : One-hundred seventy-one individuals instructed to feign ADHD were compared to 46 genuine patients with ADHD as well as 99 neurotypical controls in their reports provided on the SIRS-2. Results : Responses provided by simulators resembled those of genuine patients with ADHD on all SIRS-2 subscales with the exception of a supplementary scale tapping Overly Specified symptom reports, where a moderate effect emerged ( d = 0.88). Classification accuracy remained low, with particularly poor sensitivity (sensitivity = 19.30%). Sensitivity was higher when the decision rules postulated in the first edition SIRS were applied instead of its successor's decision model, yet this increase in sensitivity came at the price of unacceptably low specificity. Conclusion : The present results call for a disorder-specific instrument for the detection of simulated ADHD and offer starting points for the development of such a tool.